2010
DOI: 10.1016/j.semcdb.2009.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Cancer associated fibroblasts in cancer pathogenesis

Abstract: In the past century, gradual but sustained advances in our understanding of the molecular mechanisms involved in the growth and invasive properties of cancer cells have led to better management of tumors. However, many tumors still escape regulation and progress to advanced disease. Until recently, there has not been an organized and sustained focus on the “normal” cells in the vicinity of tumors. Interactions between the tumor and these host cells, as well as autonomous qualities of the host cells themselves,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
286
1
8

Year Published

2011
2011
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 340 publications
(300 citation statements)
references
References 57 publications
5
286
1
8
Order By: Relevance
“…Therefore, influences of tumor-associated acidic environments on the activity and function of these associated cells may in turn affect the progression of cancer itself. Cancer-associated fibroblasts is one of the most crucial components of the tumor microenvironment, which promotes the growth and invasion of cancer cells (52). We observed that acidic condition increased the expression of MMP2 and MMP9 in bone marrow stromal cells (data not shown).…”
Section: Discussionmentioning
confidence: 68%
“…Therefore, influences of tumor-associated acidic environments on the activity and function of these associated cells may in turn affect the progression of cancer itself. Cancer-associated fibroblasts is one of the most crucial components of the tumor microenvironment, which promotes the growth and invasion of cancer cells (52). We observed that acidic condition increased the expression of MMP2 and MMP9 in bone marrow stromal cells (data not shown).…”
Section: Discussionmentioning
confidence: 68%
“…These data suggest that MSC conditioning with T 3 or T 4 and/or T 3 or T 4 treatment of patients could serve as an effective tool to enhance MSC migration and engraftment in tissue-engineering and gene-delivery approaches. At the same time, it should be taken into account that the stimulatory effect of iodothyronines, shown in our study, on the differentiation of MSCs towards CAFs that are known to support a microenvironment that drives tumour progression and metastasis, could enhance tumour growth (Franco et al 2010). However, depending on the approach used, MSCbased cancer gene therapy can include the destruction of exogenously applied engineered MSCs in the context of therapy, which is likely to overcome any endogenous tumour-promoting effects of adoptively applied MSCs.…”
Section: Discussionmentioning
confidence: 87%
“…One of the characteristics of the tumor stroma is the emergence of a mesenchymal-specific cell called myofibroblast (27). Both clinical and experimental data support the hypothesis that myofibroblasts may modulate growth, invasion and metastasis (28)(29)(30)(31)(32)(33).…”
Section: Discussionmentioning
confidence: 91%